2006
DOI: 10.1093/jac/dkl275
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic use among children in British Columbia, Canada

Abstract: Overall antibiotic use has declined in children; however, there is increased use of macrolides which may have ramifications on macrolide-resistant streptococci, including Streptococcus pneumoniae and group A streptococci. A large proportion of antibiotic use in children is for upper respiratory tract infections and bronchitis, indications where there is a high likelihood that the aetiology is viral rather than bacterial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
40
0
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 22 publications
4
40
0
1
Order By: Relevance
“…In similar research of paediatric antibiotic use in the USA and Canada [19][20][21], the use of recommended antibiotics has been found to be decreasing. The proportion of firstline antibiotics within the DU90% segment according to the DDDs in each hospital showed a decreasing trend during 2002-2006 (see Fig.…”
Section: Discussionmentioning
confidence: 96%
“…In similar research of paediatric antibiotic use in the USA and Canada [19][20][21], the use of recommended antibiotics has been found to be decreasing. The proportion of firstline antibiotics within the DU90% segment according to the DDDs in each hospital showed a decreasing trend during 2002-2006 (see Fig.…”
Section: Discussionmentioning
confidence: 96%
“…The majority of outpatient prescribing is for the acute respiratory conditions pharyngitis, sinusitis and acute bronchitis, as well as for otitis media. 35 These syndromes are almost entirely caused by viruses. Several systematic reviews and meta-analyses have concluded that there is little or no benefit of antibiotics to these conditions.…”
Section: What Are the Major Reasons For Prescribing Antibiotics?mentioning
confidence: 99%
“…he azalide antibiotic azithromycin is considered to have advantageous pharmacokinetic (PK), pharmacodynamic (PD), and safety and tolerability properties if compared to the older macrolides and is extensively used for the treatment of adult and pediatric respiratory tract infections as well as skin and skin-related infections, including sexually transmitted diseases (1,2). In addition to time-dependent bacteriostatic or bactericidal activity, which it shares with most other macrolides (3,4), azithromycin can also show concentration-dependent bactericidal activity against some organisms (5) and displays an important postantibiotic effect (6).…”
mentioning
confidence: 99%